CARTRIDGE-BASED NUCLEIC ACID AMPLIFICATION TEST, AN IMPORTANT DIAGNOSTIC TOOL FOR TUBERCULOSIS BOTH PULMONARY AND EXTRA-PULMONARY TUBERCULOSIS - Udgata, Girija Shankar; DASH, SRIKANTA; MEHER, SASMITA; UDGATA, ANANYA; S, HOTA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Tuberculosis (TB) is severe infectious disease caused by Mycobacterium tuberculosis and imposes significant morbidity and mortality. Early diagnosis of active TB forms pulmonary and extrapulmonary is very important and the diagnostic methods such as culture test and Ziehl-Neelsen (ZN) stain displayed low diagnostic accuracy. Cartridge-based nucleic acid amplification test (CBNAAT) is widely used for the diagnosis of TB with good accuracy rate. Hence, the current study was commenced to assess the diagnostic usefulness of CBNAAT for the diagnosis of mycobacterium TB (MTB) and compared with ZN staining. Methods: This was a prospective study conducted on 250 sputum samples of pulmonary TB (new cases) and also patients who were receiving the treatment for TB. 5 mL of sputum sample including CSF, pericardial or ascitic fluid, pus, or lymph nodes aspirates were collected and subjected to ZN staining and CBNAAT. Results: Mean age observed was 48.12±8.76 years. 30 (12%) showed smear positive and 220 (88%) were smear negative for ZN staining. Further, samples have been subjected to CBNAAT showed 60 (24%) MTB positive, and 190 (74%) showed MTB negative. CBNAAT showed sensitivity and specificity of 91.5% and 89%. Out of 60 positives for MTB by CBNAAT, MTB has been identified in 28 patients. Conclusion: CBNAAT is a great tool in the early diagnosis of pulmonary and extrapulmonary TB.